Microfracture combined with anterior cruciate ligament reconstruction compared to isolated microfractures for osteochondral lesions - Walter, S G; Cucchi, D; Fröschen, F; Luceri, F; Schildberg, F A; Mangiavini, L; Briem, T; Thomas, T S; Salzmann, G M (Journal of biological regulators and homeostatic agents, 2020)
There is limited evidence whether increased growth-factor and stem-cell influx during bone tunnel drilling for ACL-reconstruction enhances clinical results of microfracture treatment of small cartilage defects. The goal of this study was to compare clinical and radiological results in patients treated with microfracture alone and patients treated with microfracture plus ACL-reconstruction. A total of 67 patients that were either treated with microfracture alone (primary stable knees, n= 40) or microfracture plus ACL-reconstruction (ACL deficient knees, n= 27) were included and prospectively evaluated. Subjects were preoperatively assessed radiologically using the MR-based AMADEUS-score (Area Measurement and Depth & Underlying Structures) and clinically using the Lysholm-score before the intervention. At minimum 24-month follow-up, the regenerate tissue was assessed by the MR-based MOCART-score (Magnetic resonance observation of cartilage repair tissue) and by use of the Lysholm-Tegner-score for clinical evaluation. Preoperatively both groups had similar AMADEUS-scores. The Lysholm-score was significantly higher in the microfracture group (p < 0.001). In the postoperative assessment there was a significant difference (p = 0.04) in the MOCART-score in favor of the microfracture plus ACL-reconstruction group. The Lysholm-score significantly improved (p <0.001) in the microfracture plus ACL-reconstruction group and was significantly higher than in the microfracture group (p = 0.004). Conclusion: A combination of microfracture and ACL-reconstruction leads to comparable functional results, yet superior MOCART-scores as compared to microfracture alone. ACL reconstruction enhances biological healing responses in microfracture treated cartilage and thus improves clinical outcomes by additional bone marrow influx from bone tunnels.